Genetic Analysis of Four Sexual Differentiation Process Proteins (isp4/SDPs) in Chaetomium thermophilum and Thermomyces lanuginosus Reveals Their Distinct Roles in Development - Xie, Xiang-Li; Wei, Yi; Song, Yan-Yue; Pan, Guan-Ming; Chen, Li-Na; Wang, Gang; Zhang, Shi-Hong (Frontiers in Microbiology, 2020)
Fungal sexual development requires the involvement of a large number of functional genes. Fungal genes encoding sexual differentiation process proteins (SDPs), isps, have been known for decades. isp4/SDP and its homologues function as oligopeptide transporters (OPTs), yet their roles in reproduction are unknown. Here, we genetically analyzed all four isp4/SDP homologues in the sexual species Chaetomium thermophilum and asexual species Thermomyces lanuginosus. Using single gene deletion mutants, we found that T. lanuginosus SDP (TlSDP) participated in asexual sporulation, whereas the other homologues participated in sexual morphogenesis. In complementary tests, C. thermophilum SDPs (CtSDP1-3) restored sporulation defects in TlSDP deletion strains (∆TlSDP), and their translated proteins, which were localized onto the cytomembrane, possessed OPT activity. Interestingly, CtSDP2 accumulated at the top of the hyphae played a distinct role in determining the sexual cycle, glutathione transport, and lifespan shortening. A unique 72nt-insertion fragment (72INS) was discovered in CtSDP2. Biological analysis of the 72INS deletion and DsRED-tagged fusion strains implied the involvement of 72INS in fungal growth and development. In contrast to TlSDP, which only contributes to conidial production, the three CtSDPs play important roles in sexual and asexual reproduction, and CtSDP2 harbors a unique functional 72INS that initiates sexual morphogenesis.